2009
DOI: 10.1007/s00038-009-0112-0
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and mental health: a causal pathways framework

Abstract: Different aspects of climate change may affect mental health through direct and indirect pathways, leading to serious mental health problems, possibly including increased suicide mortality. We propose that it is helpful to integrate these pathways in an explanatory framework, which may assist in developing public health policy, practice and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
526
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 726 publications
(545 citation statements)
references
References 67 publications
10
526
0
9
Order By: Relevance
“…Related research in psychology and economics has suggested that heat exposure reduces emotional wellbeing (Keller et al, 2005), increases interpersonal aggression (Anderson & Anderson, 1998;Anderson & Bushman, 2002) and diminishes life satisfaction (Connolly, 2013;Denissen, Butalid, Penke, & van Aken, 2008;Lucas & Lawless, 2013;Schwarz & Clore, 1983). Together, these findings indicate that heat exposure may adversely impact mental health and that global climate change, by increasing exposure to extreme heat, could similarly have negative consequences for mental health (Berry, Bowen, & Kjellstrom, 2010).…”
Section: Introductionmentioning
confidence: 90%
“…Related research in psychology and economics has suggested that heat exposure reduces emotional wellbeing (Keller et al, 2005), increases interpersonal aggression (Anderson & Anderson, 1998;Anderson & Bushman, 2002) and diminishes life satisfaction (Connolly, 2013;Denissen, Butalid, Penke, & van Aken, 2008;Lucas & Lawless, 2013;Schwarz & Clore, 1983). Together, these findings indicate that heat exposure may adversely impact mental health and that global climate change, by increasing exposure to extreme heat, could similarly have negative consequences for mental health (Berry, Bowen, & Kjellstrom, 2010).…”
Section: Introductionmentioning
confidence: 90%
“…The results were unexpected given hypotheses of adverse mental health impacts as a result of drought. 6,19,43 It is possible 45-61 year old women are adaptable and cope with the chronic nature of drought without showing a direct mental health effect. In support of this alternative explanation, previous research showed no mental health deficit attributable to living in an area sufficiently affected by climate events to be eligible for relief payments.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,23 Moreover, the literature suggests that CC adversely affects mental health indirectly by inflicting stressors due to natural disasters on human settlements, adverse effects on livelihood and illness. 24,25 The increase in acute and chronic mental health disorders would increase the burden on health systems. 25,26 Some severe mental illnesses could ultimately result in suicide.…”
Section: Impact On Developmentmentioning
confidence: 99%
“…24,25 The increase in acute and chronic mental health disorders would increase the burden on health systems. 25,26 Some severe mental illnesses could ultimately result in suicide. 27 Therefore, the developing countries of the SEAR would evidently face high disease burden, which needs to be accounted for while planning to combat CC challenges.…”
Section: Impact On Developmentmentioning
confidence: 99%